2019
DOI: 10.1111/scd.12379
|View full text |Cite
|
Sign up to set email alerts
|

Parent perspectives on perceived dental pain and dental caries in Saudi schoolchildren with intellectual disability

Abstract: Aims To assess dental pain among male Saudi schoolchildren with intellectual learning disabilities (ILD) compared with controls and evaluate parents’ perceptions of their children's dental pain and dental status. Methods and Results A mixed‐method cross‐sectional study of 92 male schoolchildren aged 12‐16 years was conducted at schools in Albaha, Saudi Arabia between March and May 2018. Participants were clinically examined for dental caries. Parents’ perspectives on their children's dental pain were explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…The prevalence of dental pain ranged from 1.33 to 87.8% (Ananthakrishnan et al 2001 ; Naidoo et al 2001 ). Sixteen publications reported a prevalence of more than 50% (Adeniyi and Odusanya 2017 ; Alzahrani 2019 ; Barreto et al 2017 ; Bashirian et al 2018 ; Dandi et al 2011 ; Van Dijk et al 2006 ; Hu et al 2018 ; Jürgensen and Petersen 2011 , 2009 ; Mishra et al 2018 ; Naidoo et al 2001 ; Oliveira et al 2018 ; Santos et al 2019 ; Shekhawat et al 2016 ; Shidara et al 2007 ; Soares et al 2015 ). Only ten studies reported a prevalence of less than 10% (Ananthakrishnan et al 2001 ; Booth et al 1992 ; Hardy et al 2018 ; Karibe et al 2015 ; Lemes et al 2015 ; Rupali et al 2010 ; Sarri et al 2012 ; Siegal et al 2004 ; Siqueira et al 2013 ; Sousa et al 2014 ) and 18 publications reported prevalence between 10 and 20% (Bastos et al 2008 ; Corrêa-Faria et al 2018 ; Dogar et al 2011 ; Du et al 2011 ; Evans et al 1995 ; Figueiredo et al 2011 ; Goettems et al 2018 ; Guskuma et al 2017 ; Kamran et al 2017 ; Kumar et al 2014 ; Lewis and Stout 2010 ; Maharani et al 2019 ; Misrohmasari et al 2018 ; Perera and Ekanayake 2008 ; Ratnayake and Ekanayake 2005 ; Treasure and Dever 1992 ; Vargas et al 2005 , 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of dental pain ranged from 1.33 to 87.8% (Ananthakrishnan et al 2001 ; Naidoo et al 2001 ). Sixteen publications reported a prevalence of more than 50% (Adeniyi and Odusanya 2017 ; Alzahrani 2019 ; Barreto et al 2017 ; Bashirian et al 2018 ; Dandi et al 2011 ; Van Dijk et al 2006 ; Hu et al 2018 ; Jürgensen and Petersen 2011 , 2009 ; Mishra et al 2018 ; Naidoo et al 2001 ; Oliveira et al 2018 ; Santos et al 2019 ; Shekhawat et al 2016 ; Shidara et al 2007 ; Soares et al 2015 ). Only ten studies reported a prevalence of less than 10% (Ananthakrishnan et al 2001 ; Booth et al 1992 ; Hardy et al 2018 ; Karibe et al 2015 ; Lemes et al 2015 ; Rupali et al 2010 ; Sarri et al 2012 ; Siegal et al 2004 ; Siqueira et al 2013 ; Sousa et al 2014 ) and 18 publications reported prevalence between 10 and 20% (Bastos et al 2008 ; Corrêa-Faria et al 2018 ; Dogar et al 2011 ; Du et al 2011 ; Evans et al 1995 ; Figueiredo et al 2011 ; Goettems et al 2018 ; Guskuma et al 2017 ; Kamran et al 2017 ; Kumar et al 2014 ; Lewis and Stout 2010 ; Maharani et al 2019 ; Misrohmasari et al 2018 ; Perera and Ekanayake 2008 ; Ratnayake and Ekanayake 2005 ; Treasure and Dever 1992 ; Vargas et al 2005 , 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are higher than those reported among SHCN children in Brazil (68.75%) [ 20 ], KSA (56.7%) [ 8 ], and Bangladesh (55.6%) [ 6 ]. However, they are not surprising when the prevalent nature of dental caries in Saudi Arabia is considered among SHCN and healthy children (27.4–79%) [ 5 , 7 , 18 , 22 , 31 , 32 ]. Additionally, the present study recruited a hospital-based sample of children who were seeking treatment of pain from self-recognized oral health problems, and consequently, they were expected to have poor oral health [ 14 , 24 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not surprising considering the greater caries experience in our population, as having more decayed teeth results in greater pain and consequently more impact on the quality of life. Another explanation would be that the children in the current study neither had problems in their verbal ability nor had an intellectual disability; hence, they should be able to express their feelings of pain or discomfort and the reasons for being upset to their caregivers very well [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations